India's Role in South Asia Trade and Investment Integration - Rajiv Kumar; Manjeeta Singh (Asian Development Bank (ADB), 2009)
Recent developments in South Asian countries, especially the re-emergence of democratic governments, new growth momentum despite the global economic downturn and greater openness, warrant a fresh look at the region's prospects for economic integration. On the basis of a thorough review of the literature on potential and prospects of regional integration in South Asia and after examining the trends in intra-SAARC trade and investment flows, this paper finds that the progress in regional cooperation has been far short of potential. The paper, therefore, focuses on the `real impediments' to regional integration and on that basis makes a set of policy oriented recommendations for furthering deeper regional integration in South Asia. It also emphasizes that given its dominant size, human resources, and aspirations for a global role, India will have to take on a disproportionately larger responsibility for promoting regional cooperation in South Asia. However, regional integration will not be achieved by India's unilateral actions alone. Neighboring governments will have to respond positively to Indian initiatives for successful regional integration in South Asia.
hdl:11540/1816
Keywords: F15; 330; South Asia; economic integration; regional trade; foreign direct investment